Sequential extraction of cadmium in different soil phases and plant parts from a former industrialized area - Kaplan, Olcay; Ince, Muharrem; Yaman, Mehmet (Springer Heidelberg, 2011)
Cd concentrations in mobile phases of soil are more representative than total Cd concentration for estimating Cd bioavailability, physicochemical reactivity and mobility. In this study, selective sequential extraction procedures were used to determine Cd in different soil phases. Soil samples and plants grown in these soils were collected from a serpentine and copper-mining area in Maden-Elazig-Turkey. The extracted fractions were exchangeable/carbonate, reducible-iron/manganese oxides, oxidizable-organic matter and sulfides, and residual phases except silicates. Concentrations of Cd in soils and plant samples were determined by flame atomic absorption spectrometry and inductively coupled plasma-mass spectrometry. We found that Cd concentrations in the EDTA and NH(2)OH center dot HCl extracts are higher in most soil samples compared to the other extracts. We conclude that Cd levels in mobile phases are unexpectedly high. The observed Cd concentrations are in ranges of 0.03-3.4 mg kg(-1) for soil and 0.02-2.5 mg kg(-1) for plant parts. The percentages of cadmium up to 56% in exchangeable and carbonates fractions were observed to be significantly higher than in those values less than 2% reported in literature. This study has shown that the modified extraction method can be usefully applied to determine Cd concentrations in potentially mobile phase of soil. Furthermore, it was concluded that Brassicasea and Rumex leaves can be used as hyperaccumulator plants because their translocation factor and/or enrichment coefficient values were found to be higher than 1.0.
Keywords: Cadmium; Sequential extraction; Soil; Plant